Development of JARIPO Assisted by Adobe Animate Based on Cooperative Integrated Reading and Composition for Elementary School Students - Musyaffa, Irsyad Fadhil; Handoyo, Eko; Isdaryanti, Barokah; Purwati, Panca Dewi (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop a learning media called JARIPO (Belajar Ide Pokok), assisted by Adobe Animate, which integrates the Cooperative Integrated Reading and Composition (CIRC) model into Indonesian language learning for elementary school students. The research method used is Research and Development (R&D), following a simplified Borg & Gall development procedure up to the expert validation stage. The validation results show that the developed media is feasible for use, with a feasibility percentage of 92.85% by language experts, 97.22% by media experts, and 94.44% by subject matter experts. The developed media is considered engaging, interactive, capable of increasing learning motivation, and suitable for the characteristics of elementary school students. This learning media can teach primary idea material in Indonesian language classes and assist teachers in enhancing students' reading skills and participation.